Pedal forces, lower limb joint kinematics and kinetics in cycling with circular and non-circular chainrings - Strutzenberger, G.; Wunsch, T.; Kröll, J.; Schwameder, H. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Non-circular chainrings theoretically enhance cycling performance by increasing effective chainring diameter and varying crank velocity. Yet, scientific proof has failed to consistently reproduce the theoretical benefits in cycling trials. Therefore, the aim of this study was to analyse kinematics and kinetics between circular and two different shapes of non-circular chainrings. 14 elite cyclists pedalled at two submaximal (90 rpm: 180 W, 300 W) two-minutes cycling trials using three chainrings ranging from circular to ovality of 1.10 and 1.215. A significant increase of tangential pedal forces, sagittal ankle and hip joint moments and a significant decrease of sagittal knee joint moments were observed. Non-circular chainrings do not evidently seem to enhance performance, but facilitated conditions for muscle activation as well as a reduction of knee joint moments can occur.